Age and side-related morphometric MRI evaluation of trunk muscles in people without back pain - Valentin, Stephanie (Man Ther, 2014)
This study evaluated lumbar spine muscle volume and Muscle Fatty Infiltrate (MFI) across two age groups of healthy adults. Twenty-four participants (young group - YG: age 18-25, n = 12; mature group - MG: age 45-60, n = 12) without low back pain underwent T1-weighted axial MRI. Muscle volume and MFI were obtained from the left and right lumbar erector spinae (ES), multifidus (M), rectus abdominis (RA) and psoas (PS) muscles. For MFI, mean pixel intensity (MPI) of muscles was reported as a percentage of subcutaneous fat MPI. Within-group comparison of left and right side muscle volume was not significantly different in the YG. In the MG, right RA and ES were significantly smaller than left (RA p = 0.049; ES p = 0.03). In both groups, left PS, M and ES MFI was significantly smaller compared to the right side and left RA MFI was significantly greater compared to right side (all p <= 0.001). For M volume, 81.7-84.6% of variance was explained by age, height and Body Mass Index (BMI). For ES volume, 81.6-82.8% of variance was explained by height and BMI. Age explained 18.1%-36.0% of variance in M and ES right MFI. Therefore, age and BMI are relevant factors for extensor muscle volume, but not for flexor muscle volume. Also, age significantly influences MFI for right-sided extensors only. The age effect is apparently independent of full subjective back functionality. For future spinal muscle research, the side and muscle-specific effect of age on muscle morphology should be considered.